From structure to ecology: Interpreting Greimas’s actantial model in the Anthropocene - Max, Jonathan Irene Sartika Dewi; Ariani, Setya (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This study looks at how Greimas' actantial model, ecocriticism, and interpretive research come together to analyze indigenous stories from Southeast Asia in the context of the Anthropocene. While previous applications of the actantial model have focused on heroism, obedience, and resistance in Indonesian folklore, they have not engaged directly with ecocritical perspectives. This research seeks to bridge this gap using interpretive research guided by Ricoeur's hermeneutics. This study explores how indigenous myths construct non-human agency, positioning nature as an active participant rather than a submissive site. The actantial model is applied to narratives such as The Origin of Paddy, The Myth of Batoq Ayau, and The Legend of Hudoq Kawit, and an academic article, Circular Commoning of Dayak Bahau, revealing how actants shape environmental discourse. Additionally, this study reinterprets transitivity, expanding its scope beyond conventional constraints to position environmental actants as central figures in narrative structures. Findings indicate that integrating Greimas' narratology with ecocriticism increases one's knowledge about human-environment interdependency, offering a fresh ecocritical perspective that challenges anthropocentric ideologies. By reframing narratives to reflect mutuality between human and non-human entities, this study contributes to sustainable ecological stewardship, reinforcing the ethical responsibility essential for environmental resilience in the Anthropocene.